Prevalence and predictors of metamorphopsia after successful rhegmatogenous retinal detachment surgery: a cross-sectional, comparative study. Issue 6 (15th September 2016) - Zhou, Chuandi; Lin, Qiurong; Chen, Fenge
Abstract : Aims: To evaluate the prevalence of metamorphopsia after successful rhegmatogenous retinal detachment (RRD) surgery and determine the independent predictors of metamorphopsia. Methods: A cross-sectional, comparative study. The study included 380 eyes of 357 patients who underwent a successful RRD surgery between 2009 and 2015. The presence of metamorphopsia was tested with an Amsler grid and the foveal microstructure was scanned with high-resolution spectral-domain optical coherence tomography (OCT) at a follow-up visit. Medical records were reviewed for preoperative and intraoperative factors associated with postoperative visual recovery. Results: The mean follow-up period was 35.1±19.6 months. The prevalence of metamorphopsia in our study was 46.58% (177/380), whereas in macula-off cases this number increased to 56.69% (144/254). Stepwise logistic regression analysis indicated that younger age at the diagnosis (OR=0.97, p<0.01), preoperative macula-off status (OR=3.34, p<0.01), postoperative presence of subretinal fluid (SRF) (OR=3.58, p=0.01) and disrupted external limiting membrane (ELM) junction (OR=1.79, p=0.02) were the independent predictors for metamorphopsia after surgery. The abnormal foveal microstructures after successful surgeries mainly included six types: disrupted inner segment/outer segment (133 eyes, 35.00%), disrupted ELM (131 eyes, 34.47%), epiretinal membrane (44 eyes, 11.58%), SRF (26 eyes, 6.84%), macular hole (9 eyes, 2.37%) and cystoid macular oedema (6 eyes, 1.58%). Conclusions: Considering metamorphopsia, special attention should be paid to young patients and/or the cases with involvement of macula. High-resolution OCT is informative in detecting anatomic abnormalities after RRD surgery. The postoperative presence of SRF and disrupted ELM line are independent predictors of metamorphopsia.